Preferential utilization in vitro of iron bound to diferric transferrin by rabbit reticulocytes. - Zapolski, E J (1977)
59Fe uptake by rabbit reticulocytes from human transferrin-bound iron was studied by using transferrin solutions (35, 50, 65, 80 and 100% saturated with iron) whose only common characteristic was their content of diferric transferrin. During the early incubation period, 59Fe uptake from each preparation by reticulocytes was identical despite wide variations in amounts of total transferrin, total iron, monoferric transferrin and apotransferrin in solution. During the later phase of incubation, rate of uptake declined and was proportional to each solution's monoferric transferrin content. Uptake was also studied in a comparative experiment which used two identical, partially saturated transferrin preparations, one uniformly 59Fe-labelled and the other tracer-labelled with [59Fe]diferric transferrin. In both experiments, iron uptake by reticulocytes corresponded to utilization of a ferric ion from diferric transferrin before utilization of iron from monoferric transferrin.